(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
We focus on the minimization problem of the eigenvalue ratio for the p-Laplacian operator with Robin boundary conditions on an interval [0, π], where π = 2πp (π/p). Using variational techniques and Prüfer-type transformations, we show that the constant weight is not minimizing for the class of concave weights.